Development of interactive multimedia based on cultural literacy for Pancasila education in elementary schools - Agustian, Murniati; Jerica; Ernestya, Teresa Gita; Ekarina (Indonesian Journal of Educational Development (IJED), 2025)
One of the main objectives of the Merdeka Curriculum is to cultivate students who practice Pancasila values, including an appreciation of diverse cultures. Currently, teachers rely mostly on textbooks and YouTube videos, highlighting the urgent need for contextual, culturally literate interactive media. This study aimed to develop such media for Grade 3 elementary students using the ADDIE model. In the Analyze stage, a needs analysis was conducted with 20 teachers and 20 students from three elementary schools through interviews and a review of materials. The prototype was validated by media, content, and language experts, followed by one-on-one testing with three students and a broader implementation with 46 students using feasibility questionnaires. This evaluation of the multimedia yielded positive results, with respondents scoring it 85.65%, 81.85%, and 82.17% for presentation, content, and navigation, respectively, all in the excellent category. This shows that the designed interactive multimedia is suitable to be used for both classroom and independent learning. This study addresses a gap in the previous research, which primarily focused on interactive multimedia for STEM classes. Thus, we recommend a wider adoption of such contextual, interactive multimedia for a diverse range of subjects, as well as further research on its impact on students’ cultural literacy.